Diffuse Lamellar Keratitis: Confocal Microscopy Features of Delayed-Onset Disease. Issue 6 (November 2015) - Rana, Mrinal; Adhana, Parul; Ilango, Balasubramanium
Abstract : Objective: Diffuse lamellar keratitis is a fairly uncommon complication of laser in situ keratomileusis (LASIK) that usually occurs within 1 week of surgery. It is described as an inflammatory reaction in the lamellar interface characterized by a diffuse, white granular lamellar keratitis. Progression of the keratitis can result in scarring and significant visual loss. We report a case of bilateral diffuse lamellar keratitis (DLK) of delayed onset and look at confocal microscopic features of corneal interface. Case report: A 35-year-old male patient was referred with visual concerns and red eye. The patient had undergone LASIK procedure for high myopia 3 months previously. A detailed examination revealed a clinical presentation of DLK. A thorough account of the past revealed no pertinent medical history or risk factors for delayed-onset DLK after LASIK. The patient was put on topical antibiotics (ofloxacin, Exocin 3 mg/mL) and topical steroids (prednisolone acetate 1%, Pred Forte). Because of poor response to treatment, an interface washout was carried out and treatment with Pred Forte was continued. This helped in resolution of the condition in both eyes with residual faint, diffuse, corneal haze. Confocal microscopy was carried out before and after interface washout to assess features of DLK at cellular level after a delayed onset. Conclusions: The presence of inflammatory cells along with interface debris was noted in our case, which is unusual in stage 3 DLK with a delayed presentation as reported in literature. Although it is difficult to confirm without histology the type of inflammatory response seen, it is advocated that delayed presentation should also be treated quite intensively with steroids and any progression should be dealt with lifting up of the flaps to carry out interface washout.